Weight Watchers make it in minutes : (Hungry Minds, 2001)
The most trusted name in weight loss makes healthy eating fast and delicious. Perfect for everyone who thought they were too busy" to cook healthy food, these meals are ready in 15, 20, or 30 minutes -- just pick the time frame that fits your schedule. The wide range of recipes will please everyone, from fussy kids to gourmets. Sample Pierogies with Creamy Mushroom and Sherry Sauce, Berries and Cream Blintzes, Pepper-Crusted Flank Steak with Cucumber Relish, Cuban Sandwiches, Easy Paella, Tuna Panzanella and Wild Mushroom Risotto."